Consumers' Knowledge, Attitudes, and Practices Toward Calorie Labeling in Riyadh City, Saudi Arabia: A Cross-Sectional Assessment - AlShehri, Nouf M.; AlMarzooqi, Mezna A. (Frontiers in Public Health, 2022)
Background Menu calorie labeling is a useful means to encourage consumers to be informed about healthy eating and food choices. It is projected as an innovative method that will change the food environment and increases consumers' awareness of calories. Objective This study aims to determine the consumer's knowledge, attitudes, and practices toward menu calorie labeling in Saudi Arabia. Methods This is a descriptive cross-sectional study involving 435 consumers in Saudi Arabia. The participants filled out an online electronic survey questionnaire that assesses the demographic factors, knowledge, attitudes, practices, and barriers toward menu calorie labeling. Logistic regression was performed to determine the predictor of attitudes of consumers toward menu calorie labeling. Results Of those 435 consumers, 50.1% were men, 33% were in the age group of 30–39, and 49.4% had a bachelor's degree. The majority of the participants reported that they can understand the calorie labels that were presented on the menus of the restaurants (N = 365, 83.9%). A high percentage of participants reported that calorie labeling encourages them to choose foods with a smaller number of calories (N = 387, 89%) and supported the posting of calorie content next to the price of the food items on the menus (N = 405, 93.1%). Barriers to using calorie labels were time-consuming and low-calorie food items are usually costly. Gender and educational attainment were found significantly associated with consumers' knowledge while marital status and BMI level were found significantly associated with attitudes and practices to using calorie labels (p < 0.05). Conclusion Overall, the participants had adequate knowledge and positive attitudes about menu calorie labeling in Saudi Arabia. Menu calorie labeling may be a useful policy tool for promoting healthy eating habits and appropriate caloric consumption.